RESPONSE OF INDICATORS MUSCLE AND KIDNEY DAMAGE TO A HALF-DISTANCE TRIATHLON IN NON-PROFESSIONAL TRIATHLETES - Marta Camacho-Cardenosa; Carmen Crespo; Alba Camacho-Cardenosa; Adrián González-Custodio; Rafael Timón; Guillermo Olcina (E-balonmano.com: Revista de Ciencias del Deporte, 2023)
Triathlon is a sport modality that has been on the rise in recent years, and represents a great physical load for the body. Therefore, the first goal of the present study was to investigate physiological response in non-professional half-distance triathlon participants regarding to muscle and kidney damage. Secondly, we evaluated the short-term recovery of this competition. Blood parameters of muscle and kidney damage of seventeen trained and experienced male triathletes were assessed before (pre) and after (post) the competition and 24h (24h REC) and 48 h (48h REC) after the individual finish. After race there were significant increases in the concentrations of creatine kinase and Total Protein (≤0.005) compared with Pre- race. A significant decrease in the total bilirubin (Δ =-24.5%; p<0.05) and Total Protein (Δ =-11.4%; p<0.05) values compared with post-race were shown 24h after race finish. At 48h of recovery, Total Protein decrease significantly compared with post- (Δ =-10.8%; p<0.05) and shown lower values compared with Pre- race (Δ =-5.7%; p<0.05). Significant muscle damage is caused in non-professional triathletes as result of half-distance race competition and 48h of recovery could be not sufficient to the decrease of serum creatine kinase.